A tailored surgical approach to the palpable undescended testis. Issue 1 (February 2019) - Neheman, A.; Levitt, M.; Steiner, Z.
Summary: Introduction: Orchiopexy for a palpable undescended testis can be approached through a traditional inguinal incision or trans-scrotally. Despite the possible advantages of the scrotal approach, including reduced postoperative pain and shorter recovery, it is not consistently advocated. Objective: The objective of this study was to present the experience with a tailored approach to orchiopexy based on physical findings. Study design: This is an extended case series. Materials and methods: The mobility of the testis as described at examination under anesthesia informs the choice of surgical approach. If a 'low' palpable testis (defined as testis that can be manipulated to the scrotum) was found, a scrotal approach was used. In cases of 'high' palpable testis (testis that cannot be manipulated to scrotum), the inguinal approach was used. Success was defined by location and size of the testis 3 months after surgery. Results: A total of 259 orchiopexies were performed in 181 boys (78 bilateral). Scrotal approach was used in 125 (48%) and inguinal in 134 (52%) orchiopexies. Operative time was significantly shorter for the scrotal approach, 25 min vs. 40 min for inguinal orchiopexy ( P  < 0.05). The overall success rate was 98% with no statistical difference between the groups. Three children from the inguinal group and two from the scrotal group required an additional procedure for persistent undescended testis. The rates of testicular atrophy and hypotrophic testis were higher in the inguinal group than the scrotal group (5/134 vs. 0/125; P  < 0.05 and 17/134 vs. 6/126; P  < 0.05, respectively). Discussion: The substantial cohort of patients selected for trans-scrotal orchiopexy experienced success rates and rates of atrophic and hypotrophic testis comparable with those found in the published literature. Furthermore, trans-scrotal operative times were significantly lower than those of inguinal procedures, and less patients required re-operation in the trans-scrotal group. Limitations of this study include significantly higher age at operation in trans-scrotal patients and a difficulty accurately classifying hypotrophic testes. Furthermore, the higher atrophic rate in the inguinal group vs. the scrotal group likely reflects the vulnerability of a testis that is located higher and not the superiority of the scrotal approach. Conclusion: This tailored approach to a palpable undescended testis appears simple, safe, and effective, providing high success rate with marginal complications. It is considered a preference in cases of low undescended testis, whereas the standard two-incision inguinal orchiopexy may better serve those with high undescended testis.Summary Table Characteristics/Outcomes Inguinal orchiopexy ( n  = 134) Scrotal orchiopexy ( n  = 125) P value Patient characteristics  Median age at operation (years) 1.3 2.8 P  < 0.05  Right testis/Left testis 72/62 60/65 NS  Concomitant hypospadias 8 5 NS Operative outcomes  Need for re-operation 3 (2.2%) 2 (1.6%) NS  Testicular atrophy 5 (3.7%) 0 P  = 0.02  Partial testicular atrophy 17 (12.7%) 6 (4.8%) P  = 0.025